LARANGAN TRADISI PERKAWINAN ADAT JAWA : JILU (SIJI JEJER TELU) - Nopriyanti Nopriyanti; Muhammad Nurwahidin; Sudjarwo Sudjarwo (Bajang Institute, 2022)
Marriage or often referred to as marriage is one of the worship that goes through a very solemn and sacred procession, following the provisions set by religious law. In its implementation, it is also inseparable from the traditions, customs and culture of the community which are sometimes still preserved and developed. One of the prohibitions is Jilu marriage, it is between first (nomer siji) child and third (nomer telu) child, because according to tradition beliefs it makestroubles and turmoil in the household. This article uses the Systematic Literature Review (SLR) method. Looked for the articles was through by two databases, these are Garuda and Google Scholar which examines about the marriage, the prohibition of Javanese traditional marriages and the philosophy of science about the prohibition of jilu marriage. This study show if the prohibition of jilu marriage is only a myth in community who has been believed for young generation as the result. So, jilu marriage can still be carried out because the happiness of being in a household is not determined by the number of births in the family.